Customer Experience Management – Eine qualitative Studie zur Umsetzung in der Versicherungsbranche - Klopfer, Lisa-Marie; Steul-Fischer, Martina; Zitzmann, Armin (Zeitschrift für die gesamte Versicherungswissenschaft, 2022)

Customer Experience Management – Empirische Studien zur Implementierung, Evaluation und Optimierung mit Fokus auf die Versicherungsbranche - Klopfer, Lisa-Marie (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2024)

Die Macht der Weiterempfehlung. Weiterempfehlungsprogramme als vielversprechende Alternative der Neukundenakquise und Kundenbindung - Klopfer, Lisa-Marie; Steul-Fischer, Martina (Vb Versicherungsbetriebe, 2022)

Evaluating Customer Experience Management in the Insurance Industry – Empirical Studies of Company and Customer Perspectives - Klopfer, Lisa-Marie (Marketing - Forschung und Praxis - Journal of Research and Management, 2024)

Exploring the influence of submission devices on customer referral creation and receiver reactions in customer referral programs - Wolf, Lukas; Klopfer, Lisa-Marie; Steul-Fischer, Martina; Reinsperger, Maximilian (Journal of Consumer Behaviour, 2024)
Customer referral programs (CRPs) are considered an effective means of customer acquisition through which firms stimulate existing customers to refer services and products to potential new customers. Digitalization and technological developments have led to the common practice of using digital devices like smartphones or laptops to create and submit customer referrals. This is the first study to investigate the influence of submission devices in CRPs from both the sender's and receiver's perspective. Based on four experiments, we demonstrate that smartphone-generated referrals are shorter and less positive than those composed on laptops/PCs. These differences in text length and valence negatively influence receiver responses, leading to lower purchase intentions due to the perceived usefulness of the referral mediating this relationship. Our findings underscore the important role of submission devices for online referral behavior and contribute to the growing body of research on device-mediated consumer behavior, offering crucial insights to optimize the promotion and design of CRPs.<br

How digital devices shape online recommendations - Klopfer, Lisa-Marie; Wolf, Lukas; Steul-Fischer, Martina (Proceedings of the European Marketing Academy, 52nd, 113943, 2023)

Optimierung des Customer Experience Managements durch die Nutzung von Speech Analytics in der Versicherungsbranche - Klopfer, Lisa-Marie; Meier, Giulia; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2024)

The influence of the used device on recommendation behavior online - Klopfer, Lisa-Marie; Steul-Fischer, Martina; Wolf, Lukas (2022)

Weiterempfehlungsprogramme: Die Wirkung des Akquisitionskanals und der Prämienaufteilung auf den Erfolg von Weiterempfehlungen - Klopfer, Lisa-Marie; Steul-Fischer, Martina (Zeitschrift für die gesamte Versicherungswissenschaft, 2020)
Referral programs are established as a marketing tool in the insurance industry, as they offer an effective and cost-efficient alternative to traditional methods of customer acquisition and retention, such as direct marketing. Previous research on referrals and referral reward programs primarily focused on the referral likelihood of existing customers. However, successful referrals also require the willingness of the recipient to accept the referral. This empirical study therefore focuses on the referral recipient and the determinants of referral acceptance. The results reveal that customers who have been acquired through a company’s referral reward program (acquisition channel) generate a higher likelihood of successful referral compared to customers acquired through other marketing activities (e.g. direct marketing). Furthermore, sharing the referral reward between sender and receiver of the referral leads to a higher likelihood of successful referral than rewarding the referrer only (reward allocation). This effect is mediated by the perceived fairness of the reward allocation.
CRIS-Team Scopus Importer:2020-07-10